FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA PARTISIPASI POLITIK MASYARAKAT PADA PEMILU LEGISLATIF TAHUN 2014 DI DESA PAUH KECAMATAN MORO KABUPATEN KARIMUN - Azura Astika; Sri Erlinda; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was motivated by his many communities that did not participate in legislative elections, especially in the village of Pauh as many as 415 people (42.13%). The problems in this study is whether the factors affecting low public political participation in legislative elections in 2014 in the village of Pauh Subdistrict Moro Karimun. This study aims to determine the factors that influence people's political participation in legislative elections in 2014 in the village of Pauh Subdistrict Moro Karimun. By using the technique according to Suharsimi Arikunto obtained 67 votes as a community sample of this research. Data collection techniques through the inquiry, documentation, interviews and literature. The results of this research are the main factors causing Pauh Village community do not participate in legislative elections that cynicism factor percentage that is equal to 73.88%. Then in one after another by a factor stimulating the participation that is equal to 73.14%. Furthermore, political awareness factor that is equal to 68.66%. Further factors of social and economic status that is equal to 62.31%. And the last factor is the weakest apathy factor that is equal to 57.96%. Key Words: Participation In Politics, Elections